Democracia e cidadania - abordagem crítica sobre a atuação das escolas do legislativo no município de Manaus - AM - Silva, Hérika Cardoso da (2021)
Democracy and citizenship is a subject that requires a path of interdisciplinary reflections capable of promoting a critical analysis of society at different historical moments and on different points of view in the light of theories that combine such as: sociology, philosophy, social psychology, psychoanalysis society, contemporary social phenomena, reflection on history and civilization. The study is inserted in the theme of Democracy and Citizenship: a critical approach to the performance of the ALEAM and CMM schools in Manaus-AM. The justification came due to the on-site visit of the researcher in the Internship Visit Program (EV) offered by the legislature school of the Chamber of Federal Deputies (CDF) in 2016, which aroused interest in the topic. The research problem questions the priority of schools in legislatures in youth protagonism actions aimed at students in basic education to the detriment of higher education. The hypothesis referred to the deduction of resistance to insert the participation of university students in the existing educational program. Thus, the general objective was to analyze the effectiveness of democracy and citizenship in the performance of ALEAM and CMM legislative schools, in the city of Manaus-AM. The specific objectives: to identify the effectiveness of democracy and citizenship in the performance of the legislative schools of ALEAM and CMM, Manaus-AM; investigate the student's interest (ESO and PPGICH-ESAT) in participating in activities in legislative schools (ALEAM and CMM); to compare the actions (youth protagonism) promoted by the schools of the legislature (ALEAM and CMM) vis-à-vis the schools of the legislatures of Brazilian assemblies and chambers from other regions between the years 2016 to 2019. The methodological procedure of the study is of a quantitative and qualitative nature, with methods of indirect, descriptive, comparative and critical approach based on bibliographic and documentary surveys (based on legislation, institutional norms). The results show the dilemmas to be faced in the democratization of public spaces and in the full exercise of citizenship that does not happen on the margins of education. This, in turn, has been one of the tools of legislative schools as they include educational programs called the “Citizen Education Program” that enable learning experiences related to democracy, politics, ethics and citizenship. Considerations: the research contributed to the understanding of Amazonian society about the performance of Legislative schools in Brazil, especially schools in the city of Manaus, whose effectiveness of democracy and citizenship can be considered one of the many dilemmas to be faced in the democratization of public spaces and in the full exercise of citizenship, since the social relationship intended by schools of the Legislative in terms of approximation with society still suffers from effective popular participation.